A critical look at the influence of TikTok videos on the reading and speaking proficiency of FL undergraduates - khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
Currently, the immersion of technology into language education has surpassed the mere provision and utilization of digital tools in language pedagogy to reshape the fundamental nature of language acquisition and instruction. While technological tools have facilitated the production and consumption of diverse and engaging multimedia content, these multimedia materials, such as videos, podcasts, and interactive simulations, have the potential to augment language learning resources significantly. This study provides a critical analysis of the influence of TikTok videos on the reading and speaking abilities of undergraduate students studying foreign languages. Meanwhile, emphasis is also placed on relevant features found on the TikTok platform that serve to enhance reading and speaking proficiency. Additionally, the study aims to identify any possible positive or harmful effects that may arise from the use of TikTok videos in language education. A quantitative methodology was used to execute the main objective of this study. This method includes the use of questionnaires as data collection techniques to get large quantities of data. On the other, the 50 respondents who took part in this study are currently foreign language students, purposively selected from different locales. However, based on insights shared by the research participants, relevant data was extracted to form the basis of this research. The results demonstrate a significant correlation between language learners' proficiency and the use of the novel technical features on the TikTok platform. Additionally, the use of TikTok has a substantial impact on the improvement and engagement of language students in the acquisition of language skills due to its enjoyable and captivating features.